Tax Policy and Reform for Foreign Direct Investment in Developing Countries. (IMF Working Papers; Working Paper ;, 1990)
This paper identifies tax factors in 21 developing countries that have an impact on foreign direct investment flows. It categorizes those factors into issues associated with tax coordination; tax rates and rate structures; and composition of the tax base. Recent actions by countries reveal no clear pattern in their attempts to increase tax coordination, while many have reduced corporate tax rates and stream-lined tax incentives. However, broad-based tax reform is lacking in most, leaving room for further possibilities in tax reform for attracting foreign investment. The paper also addresses nontax factors that can be instrumental in attracting foreign investment.